Effect of Gelatinization Temperature on the Physical Properties of Porang (Amorphophallus oncophyllus) Starch Bioplastics with Sorbitol Plasticizer - Sudiati; Ayu Mitri; Maghfirah, Awan; Brahmana, Kurnia (Journal of Technomaterial Physics, 2023)
Bioplastics are plastics that can be used like conventional plastics but can be more easily decomposed in the soil. Studies have been conducted to determine the effect of temperature variations in the gelatinization of porang starch on the manufacture of bioplastics with sorbitol plasticizers on their characterization. In this study, bioplastics have been produced which are made with variations in the composition of starch: chitosan (30:70) %, (40:60) %, (50:50) %, (60:40) %, and (70:30) % with the addition of sorbitol as a plasticizer and heating process at gelatinizing temperature variations of 70 ° C, 80 ° C, and 90 ° C. The results showed that the variation in gelatinization temperature affects the thickness, density, and absorbency of bioplastic water. Where the higher the temperature of gelatinization, the thickness of the bioplastics will decrease, the density of bioplastics will increase, and the absorption of bioplastic water decreases.